Ten weeks of Capsicum annuum L. extract supplementation did not change adipose tissue-derived hormones, appetite, body composition, and muscle strength when combined with resistance training in healthy untrained men: A clinical trial study - Moura e Silva, Vilton E.L. [UNESP]; Panissa, Valéria L.G. [UNESP]; Cholewa, Jason M.; Vieira, Matheus Mesquita [UNESP]; Antunes, Barbara M. [UNESP]; Moura, Rayane C.; Rossi, Priscila A.Q. [UNESP]; Santos, Marcos A.P.; Lira, Fabio S. [UNESP]; Rossi, Fabrício E. [UNESP] (Elsevier, 2024)
Capsiate (CAP) is a nonpungent capsaicin analog (Capsicum annuum L. extract) that has been studied as a potential antiobesity agent. However, the interaction between chronic CAP supplementation and resistance training is not clear. The purpose of this study was to examine the changes in adipose tissue–derived hormones, body composition, appetite, and muscle strength after 10 weeks of resistance training, combined with chronic CAP supplementation in healthy untrained men. We hypothesized that CAP could induce higher benefits when combined with resistance training after 10 weeks of intervention compared to resistance training alone. Twenty-four young men (age, 22.0 ± 2.9) were randomized to either capsiate supplementation (CAP = 12 mg/day) or placebo (PL), and both groups were assigned to resistance training. Body composition, leptin and adiponectin concentrations, subjective ratings of appetite, energy intake, and exercise performance were assessed at before and after 10 weeks of progressive resistance training. There was a significant increase in body mass (P <.001), fat-free mass (CAP: 58.0 ± 7.1 vs. post, 59.7 ± 7.1 kg; PL: pre, 58.4 ± 7.3 vs. post, 59.8 ± 7.1 kg; P <.001), resting metabolic rate (CAP: pre, 1782.9 ± 160.6 vs. post, 1796.3 ± 162.0 kcal; PL: pre, 1733.0 ± 148.9 vs. post, 1750.5 ± 149.8 kcal; P <.001), maximal strength at 45 leg press (P <.001) and bench press (P <.001) in both groups, but no significant (P >.05) supplementation by training period interaction nor fat mass was observed. For subjective ratings of appetite, energy intake, leptin, and adiponectin, no significant effect of supplementation by training period interaction was observed (P >.05). In conclusion, 10 weeks of resistance training increased total body weight, muscle mass, and maximum strength in healthy untrained men; however, CAP supplementation (12 mg, 7 days per week) failed to change adipose tissue–derived hormones, appetite, body composition and muscle strength in this population. Registered under Brazilian Registry of Clinical Trials (RBR-8cz9kfq).
Keywords: Adipokines; Body composition; Capsaicin; Pre-workout; Strength training